Potential antitumoral effects of SRPK1 inhibition through modulation of VEGF splicing in pituitary somatotroph tumoral cells - Treppiedi, Donatella; Di Bari, Sonia; Mangili, Federica; Barbieri, Anna Maria; Di Muro, Genesio; Locatelli, Marco; Mangone, Alessandra; Peverelli, Erika; Mantovani, Giovanna (Frontiers in Endocrinology, 2025)
Alternative splicing is a crucial mechanism of gene regulation that can be dysregulated in cancer. In pituitary neuroendocrine tumors (PitNETs), alteration in the serine/arginine-rich splicing factors (SRSFs) has been reported. SRSFs phosphorylation and activation is mediated by serine-arginine protein kinase 1 (SRPK1). SRPK1 is considered a proto-oncogene and its inhibition by small molecule inhibitors SRPIN340 and SPHINX31 have shown antitumoral effects via the SRPK1-SRSF1-VEGF pathway modulation in different cancer types. No previous studies have evaluated SRPK1 inhibitors in pituitary tumors. The present work explores the antitumoral effects of SRPIN340 and SPHINX31 in rat and human GH-secreting pituitary tumoral cells. First, immunoblot results showed a reduction of SRSFs phosphorylation induced by both compounds, demonstrating the efficacy of these molecules in inhibiting SRPK1 activity. SRPIN340 reduced GH4C1 cell proliferation (-31.7 (33.6)%, p <0.05 vs control cells at 1µM), cell viability (-16.4 (27.9)%, p<0.05 vs control cells at 1µM), cell migration (-65.0 (46.3)%, p<0.001 vs control cells at 10µM) and induced cell apoptosis (+40.5 (26.6)%, p<0.05 vs control cells at 10µM). Moreover, SRPIN340 significantly decreased both transcript (-56.3 (38.6)%, p<0.01 vs control cells) and protein levels (-33.5 (3.4)%, p<0.05 vs control cells) of the pro-survival VEGF164a isoform. Similar results have been obtained with SPHINX31. Interestingly, cells incubation with the recombinant VEGF164a protein impaired the decrease of cell migration and cell viability mediated by both SRPK1 inhibitors. As for GH-secreting primary cultures from GH-PitNETs, SRPIN340 incubation resulted in reduced VEGF165a expression (-50.6% vs control cells) and GH secretion (-14.45 (8.17)%, p < 0.05 vs control cells). In conclusion, SRPK1 inhibition may represent a novel approach to exert antitumoral effects in somatotroph tumoral cells via SRPK1-SRSF1-VEGF pathway regulation.